Boosting Soybean Growth: The Role of Soil Moisture Conservation Technique and Vesicular Arbuscular Mycorrhizae in Limpopo Province, South Africa - Thosago, Setshele Standford; Mokgehle, Ngoakoana Salmina; Molatudi, Raisibe Lucy (Journal of Tropical Crop Science, 2025)
Low soil fertility and moisture stress are the primary factors affecting soybean productivity. The study aimed to evaluate the effect of vesicular arbuscular mycorrhizae (VAM) and soil moisture conservation techniques on the performance of a promiscuous soybean variety during the 2018/2019 and 2019/2020 growing seasons. Two levels of soil moisture conservation techniques (flat and closed ridges) and two levels of VAM (0 and 100 kg.ha-1) were arranged in a split-plot design within a completely randomized block design with four replications. The data collected include growth, physiological, grain yield, and yield attributes of the promiscuous soybean variety. Sole application of soil moisture conservation techniques (SMCT) and VAM showed no significant influence (p>0.05) on the number of leaves, plant height, andnumber of branches of the promiscuous soybean variety. Soil moisture conservation techniques showed significant differences (p<0.05) in pod length. The interaction effect between soil moisture conservation techniques and the application of VAM had a significant impact on plant vigor (0.75), while non-significant variations were observed in the number of branches (5.31), plant height, and the number of leaves (20.81). The interaction effect of soil moisture conservation techniques and VAM was significant (p<0.05) on shelling percentage, while a non-significant difference was observed in grain yield (1382.7 kg.ha-1). Flat planting and nonVAM application had a higher shelling percentage (40.53%). The study demonstrated that flat planting, in combination with VAM, improved plant vigor under moisture-limited conditions. Flat planting can be recommended for soybean production at Syferkuil farm in Limpopo province.